Dynamic Modeling for a Second Order System ofTanks in Series Non-interacting System Using Simulink in Matlab - Nasaruddin, Muhammad Farzal (Universiti Teknologi Petronas, 2004)
Series non-interacting tank system is a series of tank that been align together after each other. The level of both tank are the control variables in this system meanwhile the flowrate inlet and outlet of the tanks are the manipulated variables. Since a tank is design at certain limit, thus the level of the tank must always be monitored so that it would not go beyond the design level as this will give bad effect to the tank itself. Indeed it is also a safety precaution; excess level may cause spillage and spoil the tank as well as the product quality. For the purpose of study, this dynamic model has been developed to give a reliable mathematical model so that it will give an ease for future system monitoring. Level of each tank really depending on one another as the tanks is arranged in series; furthermore the level must also be controlled. In this dynamic modeling, two tanks in series have been taken as an example. This is only to grab the concept of series tank. The number oftank can be extended but still the two series tank concept is taken as a baseline. And this is the reason why this experiment is using the second order system. Simulink is the core software for this dynamic modeling. The simulation as well as the PID tuning is done using this software. The values that have been substituted in this simulation are taken from a real figure from PETRONAS in Dexter. However, there are still some assumptions have beenmade such as pumps stroke, valve opening etc. Those figures also been varied in order to study its trending. But when come to the real application, those values canbe substituted back withthe actual value from plant.